2022
DOI: 10.3389/fnagi.2022.892178
|View full text |Cite
|
Sign up to set email alerts
|

Research on Rehabilitation Training Strategies Using Multimodal Virtual Scene Stimulation

Abstract: It is difficult for stroke patients with flaccid paralysis to receive passive rehabilitation training. Therefore, virtual rehabilitation technology that integrates the motor imagery brain-computer interface and virtual reality technology has been applied to the field of stroke rehabilitation and has evolved into a physical rehabilitation training method. This virtual rehabilitation technology can enhance the initiative and adaptability of patient rehabilitation. To maximize the deep activation of the subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…At the neurophysiological level, a study by Choi et al (2020) demonstrated that event-related desynchronizations exhibited greater amplitudes with more distinct spatial features of the brain when MI is performed using a VR headset, compared to the display of the same images on a monitor. This modulation of neural activity by the degree of immersion provides important evidence for the use of VR technology in rehabilitation practice for bedridden patients ( Xie et al, 2022 ). A recent study by Köyağasıoğlu et al (2022) found that a 4-week intervention combining VR and MI significantly improved balance skills in healthy adults.…”
Section: Virtual Reality (Vr)mentioning
confidence: 96%
“…At the neurophysiological level, a study by Choi et al (2020) demonstrated that event-related desynchronizations exhibited greater amplitudes with more distinct spatial features of the brain when MI is performed using a VR headset, compared to the display of the same images on a monitor. This modulation of neural activity by the degree of immersion provides important evidence for the use of VR technology in rehabilitation practice for bedridden patients ( Xie et al, 2022 ). A recent study by Köyağasıoğlu et al (2022) found that a 4-week intervention combining VR and MI significantly improved balance skills in healthy adults.…”
Section: Virtual Reality (Vr)mentioning
confidence: 96%
“…In the other study, Xie et al (2022) developed a rehabilitation training strategy for BCI using various virtual scenes, such as static scenes, dynamic scenes, and VR scenes. They investigated the activation and recognition rates of MI in stroke patients following MI training in these three different settings.…”
Section: Background and Related Workmentioning
confidence: 99%
“…After a period of investigation and research, it is found that the use of somatosensory technology combined with motion recognition algorithm (Nakamura et al 2005) can bring more scientific and comprehensive fitness activities to the masses with low cost and efficiency, especially for schools and communities in which individuals have little demand for sports, but the base number is large. At present, most scholars' motion recognition based on somatosensory technology only stays at the theoretical stage and has not been developed and utilized, but it has been applied in related medical rehabilitation fields, such as rehabilitation equipment with virtual scene stimulation (Xie et al 2022), virtual treatment environment for upper limb stroke rehabilitation (Burke et al 2010), rehabilitation robot with adjustable posture that can design motion tracks and virtual reality rehabilitation training system based on machine vision (Chen et al 2009). For the outward bound training, there still lacks related works.…”
Section: Related Workmentioning
confidence: 99%